2011
DOI: 10.1074/jbc.m111.226605
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like Kinase1 Is Required for Recruitment of Dynein to Kinetochores during Mitosis

Abstract: Kinetochore dynein has been implicated in microtubule capture, correcting inappropriate microtubule attachments, chromosome movement, and checkpoint silencing. It remains unclear how dynein coordinates this diverse set of functions. Phosphorylation is responsible for some dynein heterogeneity (Whyte, J., Bader, J. R., Tauhata, S. B., Raycroft, M., Hornick, J., Pfister, K. K., Lane, W. S., Chan, G. K., Hinchcliffe, E. H., Vaughan, P. S., and Vaughan, K. T. (2008) J. Cell Biol. 183, 819 -834), and phosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…[23] The inhibition of Plk1 leads to mitotic entry delay followed by prometaphase arrest. [24] Recently, teams led by Kapoor and Straight have examined the effects of Plk1 inhibitors on metaphase, [25] and observed failure during contractile ring assembly and in the cleavage furrow as well as defects in RhoA localisation; these observations compare favourably with our confocal studies. In fact, the observed features suggested that the effects of 1 included mitotic arrest (Figure 5 Actually, many reports have shown that Plk1 inhibition impairs RhoA binding to other proteins, such as endothelial cell transforming complex 2 (Ect-2), which are involved in the latter stages of cytokinesis.…”
supporting
confidence: 83%
“…[23] The inhibition of Plk1 leads to mitotic entry delay followed by prometaphase arrest. [24] Recently, teams led by Kapoor and Straight have examined the effects of Plk1 inhibitors on metaphase, [25] and observed failure during contractile ring assembly and in the cleavage furrow as well as defects in RhoA localisation; these observations compare favourably with our confocal studies. In fact, the observed features suggested that the effects of 1 included mitotic arrest (Figure 5 Actually, many reports have shown that Plk1 inhibition impairs RhoA binding to other proteins, such as endothelial cell transforming complex 2 (Ect-2), which are involved in the latter stages of cytokinesis.…”
supporting
confidence: 83%
“…The enzyme responsible for phosphorylation in this system has not been identified; however, polo-like kinase (25) and casein kinase (26,27) have been reported to phosphorylate dynein IC in vitro and in Xenopus melanophores (27), and also activations of MAPK, CDK5, GSK3, and ROCK in NF1-KD PC12 cells were found in our previous study (7). Thus, these enzymes may be involved in the regulation of neurite outgrowth in NF1-KD cells.…”
Section: Discussionmentioning
confidence: 92%
“…Very similar results were observed using RO-3306 or the Cdk1/Cdk2 inhibitor III (Gavet and Pines, 2010) (Figure 2A and 2E). The Aurora A inhibitor VX680 (Harrington et al, 2004) had no significant effect, but a mild effect was observed with the Plk1 inhibitor BTO-1 (Bader et al, 2011) (Figure 2E). This could reflect a role for Plk1 in Cdk1 activation, though a more direct role in dynein recruitment is also possible (Li et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…For better visualization of NE dynein and dynein partners, cells were incubated for 1 hr in Nocodazol (10 μM) prior to fixation (Bolhy et al, 2011; Hu et al, 2013; Raaijmakers et al, 2013; Splinter et al, 2012). The following drugs were used for protein kinase inhibition: 55 μM Roscovitine (Meijer et al, 1997) (Selleck Chemicals); 0.9 μM Cdk1/2 inhibitor III (Gavet and Pines, 2010) (Calbiochem); 28 μM RO-3306 (Deibler and Kirschner, 2010; Vassilev et al, 2006) (Tocris Bioscience); 0.5 μM PD166285 (Potapova et al, 2009) (Tocris Bioscience); 0.3 μM VX-680 (Harrington et al, 2004) (Selleck Chemicals); 22 μM BTO-1 (Bader et al, 2011) (EMD Millipore).…”
Section: Methodsmentioning
confidence: 99%